Validation of Noninvasive Absolute Intracranial Pressure Measurements in Traumatic Brain Injury and Intracranial Hemorrhage. Issue 2 (3rd May 2018) - Kienzler, Jenny C; Zakelis, Rolandas; Bäbler, Sabrina; Remonda, Elke; Ragauskas, Arminas; Fandino, Javier
Abstract: BACKGROUND: Increased intracranial pressure (ICP) causes secondary damage in traumatic brain injury (TBI), and intracranial hemorrhage (ICH). Current methods of ICP monitoring require surgery and carry risks of complications. OBJECTIVE: To validate a new instrument for noninvasive ICP measurement by comparing values obtained from noninvasive measurements to those from commercial implantable devices through this pilot study. METHODS: The ophthalmic artery (OA) served as a natural ICP sensor. ICP measurements obtained using noninvasive, self-calibrating device utilizing Doppler ultrasound to evaluate OA flow were compared to standard implantable ICP measurement probes. RESULTS: A total of 78 simultaneous, paired, invasive, and noninvasive ICP measurements were obtained in 11 ICU patients over a 17-mo period with the diagnosis of TBI, SAH, or ICH. A total of 24 paired data points were initially excluded because of questions about data independence. Analysis of variance was performed first on the 54 remaining data points and then on the entire set of 78 data points. There was no difference between the 2 groups nor was there any correlation between type of sensor and the patient (F[10, 43] = 1.516, P = .167), or the accuracy and precision of noninvasive ICP measurements (F[1, 43] = 0.511, P = .479). Accuracy was [−1.130; 0.539] mm Hg (CL = 95%). Patient-specific calibration was not needed. Standard deviation (precision) was [1.632; 2.396] mm Hg (CL = 95%). No adverse events were encountered. CONCLUSION: This pilot study revealed no significant differences between invasive and noninvasive ICP measurements ( P < .05), suggesting that noninvasive ICP measurements obtained by this method are comparable and reliable.